New Paradigm in Natural Resources Management: Securing Indigenous Peoples Rights - Farida Patittingi (Hasanuddin Law Review, 2020)
The multi-decade struggle of indigenous communities in Indonesia to gain recognition of their collective rights and the reluctance of the state to act on their demands, now has come to a bright spot. The rights of indigenous peoples in natural resources management –in land and forests– get more recognition as well as protection since the Constitutional Court’s decision on forest law. The recognition of indigenous peoples and their traditional rights must be followed by exclusive rights to control and managing resources in their environment, such as land or forests, as the main source of livelihood for indigenous peoples (lebensraum). Hence, a legal policy is needed from the government that regulates and provides strict and clear recognition criteria for its existence and their rights to natural resources.